The effect of Medicaid expansion on female gynecologic cancer-related inpatient admissions - Shiva Salehian; Michael Preston; Peter Cunningham; Dipankar Bandyopadhyay; Emmanuel Taylor (Women's Health)
Background: Mortality rate of female gynecologic cancer is higher among individuals without affordable health insurance. Objectives: We determined the impact of Medicaid expansion on the number of female gynecologic-related cancer inpatient admissions in Virginia (VA) relative to North Carolina (NC), the latter of which did not expand Medicaid. Design: This quasi-experimental study was restricted to women between 18 and 64 years old admitted to general, acute, and short-term hospitals with gynecologic cancer. Methods: We used Poisson fixed-effect event study regression to examine differences in the predicted number of female gynecologic-related cancer admissions in the quarters before and after Medicaid expansion (implemented in January 2019) in VA, compared to the same period in NC. Results: Even though not significant, the predicted number of female gynecologic cancer-related inpatient admissions in VA increased by 4.8%, 4.9%, and 5.5% in the second, third, and fourth quarter of 2019, respectively, compared to the first quarter of 2019. Conclusion: Medicaid expansion in VA increased access to health services for Medicaid members, possibly due to initial pent-up demand among uninsured individuals.